Semantic variants of terms in banking sphere (in Ukrainian and English languages). - Петрина, Оксана Степанівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
Consideration is given to the polysemy phenomenon in English and Ukrainian terminology systems of banking sphere. The implicit polysemy and explicit polysemy are studied. The factors giving rise to polysemy (the process of terminologisation, metaphorization, metonymyzation, conversion) are revealed. The comparative analysis of polysemantic words of both terminology systems is conducted. The results of comparative analysis gave an opportunity to figure out common and specific features of polysemantic words in English and Ukrainian banking terminology.